Constructing active copper species in Cu-zeolites for coal-gas-SCR and elucidating the synergistic catalytic function of CuO and Cu2+ ion species. Issue 7 (26th May 2022) - Cheng, Jie; Zheng, Dahai; Dai, Chengna; Xu, Ruinian; Liu, Ning; Yu, Gangqiang; Wang, Ning; Chen, Biaohua
Abstract : Cu-ZSM-5-IE+CP exhibited excellent catalytic performance as a result of the synergistic effect between CuO and Cu 2+ species. Abstract : Coal-gas-SCR, initially proposed in this work, is a low-cost and effective strategy to eliminate NO x emission in the iron and steel industry. In this work, the Cu-ZSM-5-IE+CP catalyst prepared by liquid ion exchange combined with coprecipitation was filtered out for NO x abatement with coke-oven gas (H2, CH4, and CO). By means of XRD, TEM, H2 -TPR, EPR, UV-vis, XPS, etc., active centers of Cu-ZSM-5-IE+CP were studied. Combined with DFT calculations and ab initio thermodynamic (AIT) analyses, it was confirmed that highly dispersed CuO nanoparticles with the (111) planes exposed and [ZCuOH]/[Z2 Cu] in the Z[Cu(ii )]-6R- D 4h structure are the most possible main active motifs for the coal-gas-SCR. Moreover, the synergistic effect of Cu 2+ ions and CuO species was elucidated. In situ DRIFTS and SCR-TPD results revealed that surface species can migrate between CuO and Cu 2+ ions, which could further accelerate intermediate species (NCO, CH3 NO, and NH4 + ) formation, resulting in better deNO x efficiency.